A retrospective study of infantile-onset Takayasu arteritis: experience from a tertiary referral center in China - Jin, Jing; Zhao, Yan; Gao, Xiucheng; Wang, Panpan; Liu, Yingying; Pan, Yuting; Fan, Zhidan; Yu, Haiguo (Frontiers in Cardiovascular Medicine, 2024)
Objective Takayasu artery (TAK) is a chronic inflammatory disease that mainly affects the aorta and its major branches and is rarely reported in infants. We aimed to summarize the clinical features of infant TA (I-TA) in a tertiary care center. Methods We performed a retrospective study involving 10 infants diagnosed with TAK. A comprehensive evaluation of clinical, laboratory, radiographic features, disease activity, treatment and outcomes was carried out. Results A consecutive cohort was composed of 8 girls and 2 boys, with an age at diagnosis of 11.1 (1.7–36) months. The median time to diagnosis and the average time to follow-up were 9.5 days (2–235 days) and 10.9 (1–21) months, respectively. The most common initial manifestations were malaise (80%), fever (70%), hypertension (50%) and rash (30%). The mean Pediatric Vasculitis Activity Score (PVAS), Takayasu Clinical Activity Score (ITAS-2010) and ITAS-A scores were 2.8/63, 2.6/51, and 5.6/54, respectively. All patients had aberrant laboratory parameters. The most common lesions were in the thoracic aorta (60%) and abdominal aorta (60%). Corticosteroids combined with cyclophosphamide followed by long-term mycophenolate mofetil were initiated in most cases (70%). Biologics were attempted in 5 cases. Mortality was 40%. Conclusions It is challenging to diagnose TAK in infants in a timely manner. Considering the more vessels involved, more severe inflammation and higher mortality, aggressive treatment is warranted in infants. GCs and CYC treatment seem to be effective.